Knowledge and Practices of First Aid among Basic Education Professionals in a School in Belém, Pará, Brazil - , Larissa Satie Souza de Lima; , Dheisen Moraes Rodrigues; , Rejany Cristina Santana da Silva; , Elma Adalgisa Lima Teixeira; , Danielle Iasmim Sarmento Pinheiro; , Elyson Fernanda Ribeiro da Conceição; , Ryane Oliveira Neves; , Wênia Gilmara da Silva; , Cielma Amaral da Silva; , Thayrla dos Santos Duarte; , Maria Luisa Freitas Rodrigues Lima; , Acsa Lino Geraldo; et al. (Archives of Current Research International, 2025)
Introduction: School life is an important part of children's lives, which has a direct impact on their physical and mental health. School is an environment where accidents can occur with children. First Aid must be the immediate care provided to a victim after an accident. This initial care generally occurs by professionals who work in schools, making them responsible for correct and effective care actions. Part of the knowledge of health promotion and prevention activities are strategies to reduce the impact of illnesses and emergencies on society. Methods: This is descriptive fieldwork, with a quantitative basis for data analysis, whose collection period took place in October 2023. In a private school, all employees who worked at the educational institution were interviewed. Results and Discussion: Teachers and employees at the educational institution where the research was carried out found that 56% of professionals did not have training to provide First Aid care, although a significant percentage (56%) of these professionals had already witnessed a school accident. Thus, it was observed that, in accidents, they are usually the first to provide immediate assistance to children, making it necessary for them to feel confident and capable of carrying out an appropriate intervention. Regarding the existence of a first aid kit at school, only 5 (9.43%) said they were aware of it. Furthermore, when asked where to find this kit, 5 (9.43%) responded that they knew where to find it and the majority 11 (14.86%) responded that they did not know. Conclusion: Training education professionals with effective first aid assistance techniques is a prevention strategy that will contribute to a safer childhood. It is important to promote discussions and actions for the implementation of a preventive public policy, which guarantees the professional qualification of professionals working in basic education, and/or the insertion of nursing professionals in the school environment.